Obesity and Hyperlipidemia Modulate Alveolar Bone Loss in Wistar Rats - Cavagni, Juliano; Macedo, Isabel Cristina de; Gaio, Eduardo Jose; Souza, Andressa; Molon, Rafael Scaf de [UNESP]; Cirelli, Joni Augusto [UNESP]; Hoefel, Ana Lucia; Kucharski, Luiz Carlos; Silva Torres, Iraci Lucena da; Roesing, Cassiano Kuchenbecker (Amer Acad Periodontology, 2016)
Background: A positive association between obesity-associated metabolic disorders (e.g., hyperlipidemia and diabetes) and periodontitis has been demonstrated in the literature. This study evaluates the role of cafeteria diet-induced obesity/hyperlipidemia (CAF) on alveolar bone loss (ABL) in rats. Methods: Sixty male Wistar rats were randomly divided in four groups: control, periodontitis (PERIO), obesity/hyperlipidemia (CAF), and obesity/hyperlipidemia plus periodontitis (CAF+PERIO). Groups CAF and CAF+PERIO were exposed to a high-fat, hypercaloric diet. At week 12, periodontal disease was induced in groups PERIO and CAF+PERIO by ligatures in the upper second molar. The contralateral tooth was considered the intragroup control. Body weight and Lee index were evaluated weekly during the experiment. Serum glucose and cholesterol/triglycerides in the liver were evaluated, and percentage of ABL was measured by microcomputed tomography. Serum tumor necrosis factor (TNF)-alpha and interleukin (IL)-1 beta were evaluated by enzyme-linked immunosorbent assay at week 17. Results: Body weight, Lee index, and cholesterol/triglycerides in the liver increased in groups exposed to the cafeteria diet. Groups PERIO and CAF+PERIO exhibited a significantly higher ABL compared to control and CAF groups. The presence of obesity and hyperlipidemia significantly increased ABL in the CAF+PERIO group compared to the PERIO group (53.60 +/- 3.44 versus 42.78 +/- 7.27, respectively) in the sides with ligature. Groups exposed to CAF exhibited higher ABL in the sides without ligature. No differences were observed among groups for IL-1 beta and TNF-alpha. Conclusion: Obesity and hyperlipidemia modulate the host response to challenges in the periodontium, increasing the expression of periodontal breakdown.
Keywords: Diet; hyperlipidemias; microcomputed tomography; obesity; periodontal diseases; rats